2017
DOI: 10.1016/j.jddst.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Advances on the formulation of proteins using nanotechnologies

Abstract: Therapeutic proteins and peptides are very attractive from the pharmaceutical point of view due to their high potency and selectivity. Nonetheless, their instability and low bioavailability make their administration through non parenteral routes very difficult, a fact that hampers their efficient exploitation in therapeutics. Since the 70´s, significant amount of research in the area of drug delivery and nanotechnology has been done with the final goal of overcoming those hurdles. In particular, biodegradable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 278 publications
(427 reference statements)
0
18
0
Order By: Relevance
“…AMPs have the advantage, over organic small molecule drugs, of producing non-toxic byproducts (Loffet, 2002) and usually exhibit multiple mechanisms making the development of resistance toward them by microbes rare. Even though AMPs are often disadvantaged by their weak ability to traverse the plasma membrane to reach their intended targets, attempts by researchers to develop lipidic and polymeric nanocarriers to deliver peptides (Santalices et al, 2017) make AMPs development promising.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…AMPs have the advantage, over organic small molecule drugs, of producing non-toxic byproducts (Loffet, 2002) and usually exhibit multiple mechanisms making the development of resistance toward them by microbes rare. Even though AMPs are often disadvantaged by their weak ability to traverse the plasma membrane to reach their intended targets, attempts by researchers to develop lipidic and polymeric nanocarriers to deliver peptides (Santalices et al, 2017) make AMPs development promising.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…In this section, only a few examples are given to highlight the potential of different kinds of CDSs for this purpose. Most of the information on this topic comes from pre-clinical studies, but a number of CDSs have been developed that are in various stages of clinical testing or are available commercially, which have been reviewed by other authors [129,130]. For instance, these authors reported that liposomes have been used to encapsulate insulin, anticancer peptides, and virus antigens, but not all of these applications were for oral delivery.…”
Section: Applicationsmentioning
confidence: 99%
“…Lipid-based nanocarriers have been widely described during the last decade as ideal systems for the transport and delivery of active substances that need to be protected from enzymatic and biological degradation [ 47 , 48 , 49 ], and as an option for resolving the common solubility problems that affect lipophilic substances [ 8 , 50 , 51 ]. A mix of solid and liquid lipids is used to formulate nanostructured lipid carriers (NLCs), usually in a ratio of 70:30 [ 49 ].…”
Section: Nanosystems As Components Of Edible Coatingsmentioning
confidence: 99%